Degradation of Carbamazepine by Photo-assisted Ozonation: Influence of Wavelength and Intensity of Radiation. (4th March 2018) - Somathilake, Purnima; Dominic, John Albino; Achari, Gopal; Langford, Cooper H.; Tay, Joo-Hwa
ABSTRACT: This article presents the results of an investigation into the function of UV in a photo-assisted ozonation process for treatment of carbamazepine (CBZ) in treated domestic wastewaters. Experiments were conducted on synthetic spiked water and secondary treated municipal wastewater. Degradation of CBZ was studied for various combination of O3 dosage ranging from 4.8 to 14.4 mg/h and UV intensities with varying intensity and wavelength (UVC: λ = 254 nm and UVA: 352 nm). In synthetic spiked water, CBZ was degraded to below detectable limits within 0.5 min for ozone dose of 14.4 mg/h. The rate of degradation of CBZ increased exponentially with increase in ozone dose following a zero-order rate at each dose level. The degradation rate of CBZ in wastewater was slower compared to deionized water (DI) water by 40–75% for various doses of ozone, presumably due to the presence of organic matter remaining in treated wastewater. Optimal UV intensities for UVA and UVC were obtained as 0.62 and 0.82 mW/cm 2 for all doses of ozone in synthetic spiked water samples and UV intensities beyond this resulted in lower rates of degradation of CBZ. For photo-assisted ozonation with ozone doses of 9.6 and 14.4 mg/L, rate constants were two times higher for UVA irradiations as compared to UVC irradiation. Contrary to observations in DI water, experiments in wastewater showed increase in rate of degradation with higher UV intensities. Overall, photo-assisted ozonation was found to be appropriate for both water and wastewater treatment by exploiting the benefit of direct attack of ozone and of produced OH radicals to yield a greater extent of mineralization of CBZ.